An Upcoming Approach to Alzheimer's Disease: Ethnopharmacological Potential of Plant Bioactive Molecules - Martins, Natália; Ferreira, Isabel C F R; Heleno, Sandrina A. (Current medicinal chemistry, 2020)
Neurodegenerative disorders achieved epidemic levels in the last decades; not only elderly but also adult individuals have been increasingly affected. Among them, Alzheimer's disease is one of the most prevalent and crippling, associated with high rates of multi-morbidities and dependency. Despite the existence of a wide variety of drugs used as symptomatic treatment they have some side effects and toxicity, apart from its limited effectiveness. Botanical preparations have a secular use, being widely recommended for a multitude of purposes, such as brain health improvers. The aim of the present report is to systematize the knowledge about plant-food derived bioactive molecules with promising in vitro enzymatic inhibitory activity. Alkaloids, phenolic compounds and terpenes are the most studied phytochemicals, both derived from natural and commercial sources. In spite of its efficient activity as enzymatic inhibitors, the number of in vivo studies and even clinical trials to confirm its real bioactive potential remains scarce. Thus, it is of the utmost importance to deepen knowledge on this area, once those relevant and informative tools can significantly contribute to the promising advances on the field of Alzheimer's disease treatment.